Interpreting Ulysses data using inverse scattering theory: Oblique Alfvén waves. Issue 3 (14th March 2015) - Wheeler, Harry R.; Reynolds, M. A.; Hamilton, R. L.
Abstract Solitary wave structures observed by the Ulysses spacecraft in the solar wind were analyzed using both inverse scattering theory and direct numerical integration of the derivative nonlinear Schrödinger (DNLS) equation. Several of these structures were found to be consistent with soliton solutions of the DNLS equation. Such solitary structures have been commonly observed in the space plasma environment and may, in fact, be long‐lived solitons. While the generation of these solitons may be due to an instability mechanism, e.g., the mirror instability, they may be observable far from the source region due to their coherent nature.